Right ventricular function in rats with hypoxic pulmonary hypertension - Kolár, F; Ostádal, B (Pflugers Archiv, 1991)
The function of the hypertrophic right ventricle (RV) was studied in adult rats with hypoxic pulmonary hypertension induced by intermittent high-altitude (IHA) exposure. The isolated RV working heart preparation that was employed enabled us to estimate ventricular contractile and pump performance under controlled loading conditions. In rats exposed to IHA hypoxia the elevated RV systolic pressure and maximum rate of pressure development were observed at various levels of preload or afterload. The peak indices of mechanical performance were almost doubled in these animals when compared with the normoxic group, while the index of contractility remained unchanged. Maximum ventricular performance was found to be a linear function of the relative RV weight. No evidence of RV pump dysfunction was detected in rats exposed to IHA; moreover, the ability of the ventricle to maintain cardiac output against increased pulmonary resistance was markedly improved. The prevention of tricuspid regurgitation by using an artificial valve did not influence the functional curves and the peak ventricular performance. The regression of hypertrophy was accompanied by a reversal of ventricular function to control values, except for the persisting slight increase of peak RV pressure. It may be concluded that the increase of the RV mass in IHA-exposed rats serves to improve maximum ventricular performance, which aids in overcoming and elevated pulmonary resistance without disturbing the pump function.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; Rats; Cardiomegaly; krevní tlak; Altitude Sickness; Hypertension, Pulmonary; mužské pohlaví; regresní analýza; kardiomegalie; krysa rodu Rattus; Body Weight; Organ Size; velikost orgánu; plicní hypertenze; výšková nemoc; zvířata; Blood Pressure; tělesná hmotnost; Regression Analysis; Male; Animals